The influence of Arabic on Indonesian language - Zainul Arifin (Fakultas Ilmu Budaya, Universitas Jambi, 2017)
the preparation of any educational material to teach Arabic to non-native speakers requires preliminary studies, Among the important studies is the study of the basic vocabularies, which will be based on the educational material, and this requires the preparation of lists of the influence of Arabic on Indonesian language, especially basic Arabic vocabulary andcommon Arabic vocabulary in loanwords between the languages ​​of these vocabularies. Some researchers have confirmed that this loanwords between the Arabic language and the student’s language facilitates easy input to teach Arabic in the first lessons.Rushdie Ahmed To'eima believes that start using this loanwords is harvested a lot of good. The use of these terms in the first lessons is acceptable input and educationally well but it does not prevent to use basic necessary vocabulary and common Arabiclater. Emphasizing the importance of studying the common Arabic words in the student’s language - or by the other Arab vocabulary borrowed in his own language -,symposium held in Rabat in March 1980 recommended when write books teaching Arabic for Speakers of Other Languages to choose the vocabulary and structures in the preparation of educational materials from loanwords between arabic and student’s language or languages that used in islamic countries.